Application of the Concept of Healing Environment-in the Design of the Drug Rehabilitation Center in Bali - Nugraha, I Made Hari Wangsa; Rajendra, I Gusti Ngurah Anom; Manik, I Wayan Yuda (Journal of A Sustainable Global South; Vol 2 No 2 (2018): August 2018DO - 10.24843/jsgs.2018.v02.i02.p02, 2018)
A drug addict (narcotics, psychotropic drugs, and other addictive materials) have a very rapid development in many countries. Country Indonesia included in the country with the number of drugs users are growing rapidly every year, so it needs a facility that is the drug rehabilitation. Drug addict rehabilitation center in Bali is a facility that hosts a drug ad-dict in order to recover the health of body, emotions, mind, and soul. Drug addict rehabilitation facilities have on site medical and non-medical health required for restoring and treating drug addicts and it also helps the Government pro-gram to reduce the drug addict. Drug rehabilitation center is a healing environment designed aiming to accelerate the healing process ang providing service for drug addicts. To achieve these goals, the process of designing a drug addict rehabilitation centre implemented the concept of the healing environment where in this design, the healing process is obatained through the rehabillitan not only medical but also parties obtained from the environment around the rehabili-tan used by rehabillitan as on object design. Index Terms — drug addict, rehabilitation center, healing environment.